Two new genera of Conopidae from the Afrotropical and Neotropical Region (Diptera) - Stuke, Jens-Hermann (Zootaxa, 2007)
The monotypic genera Jelte gen. nov. (neotropical) and Tammo gen. nov. (afrotropical) are described and compared to Pleurocerinella Brunetti, 1923.